2019
DOI: 10.1111/jpn.13271
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of plant essential oil improves growth performance, intestinal morphology and health in weaned pigs

Abstract: The present study was conducted to explore the effect of plant essential oil (PEO) on growth performance, intestinal morphology and health in weaned pigs. Twenty‐four weaned pigs were assigned into four groups fed with a basal diet (CON) or basal diet containing PEO at a concentration of 50 (PEO50), 100 (PEO100) or 200 ppm (PEO200). After 21 days, pigs were slaughtered and blood and tissue samples were collected. Result showed that PEO200 group significantly increased the average daily gain (ADG) compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Overall, the groups that received OCE, MOCE, and MOC showed lower Cd, higher Vh, and higher Vh : Cd than the control group. At the same time, IAA values were numerically higher in all treated groups compared to the control group; nevertheless, statistical significance was only achieved in the ileum samples from group C. The improvement of intestinal histomorphology associated with the incorporation of different phytogenic compounds including thymol, carvacrol, and eugenol in the swine diet has been described several times 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the groups that received OCE, MOCE, and MOC showed lower Cd, higher Vh, and higher Vh : Cd than the control group. At the same time, IAA values were numerically higher in all treated groups compared to the control group; nevertheless, statistical significance was only achieved in the ileum samples from group C. The improvement of intestinal histomorphology associated with the incorporation of different phytogenic compounds including thymol, carvacrol, and eugenol in the swine diet has been described several times 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, disaccharidases activity showed higher values in samples from treated than from control groups, though statistically significant differences were only observed for the group receiving MOCE. The increase of digestive enzymes activity in animals fed diets supplemented with phytogenic compounds has been described in poultry 28 , 30 and pigs 3 , 29 . In our work, a higher enzymatic activity was accompanied by a higher Vh : Cd.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 36 ) found that orange EO could regulate the intestinal microbiota of mice by increasing the relative abundance of Lactobacillus and reducing the presence of bacteria producing short chain fatty acids. EOs with the active ingredient of 13.5% thymol and 4.5% cinnamaldehyde markedly up-regulated the expression levels of occludin in the duodenum, which suggested that EOs maintained the integrity of intestinal barrier ( 37 ). Zou et al ( 38 ) found that pretreatment with oregano EO could significantly decrease the expression of occludin and ZO-1 in porcine epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The vacuum tubes of EDTA-Na 2 were immediately placed on ice for analysis of blood biochemistry. Blood samples with sodium heparin were centrifuged (3000g, 15 min, 4°C) to obtain plasma samples, and stored at −80°C for further analysis (Su et al 2020).…”
Section: Blood Samplementioning
confidence: 99%